2016
DOI: 10.1177/0095244316639634
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties, thermal behaviors and oil resistance of epoxidized natural rubber/multiwalled carbon nanotube nanocomposites prepared via in situ epoxidation

Abstract: Epoxidized natural rubber (ENR)/multiwalled carbon nanotube (MWCNT) nanocomposites were prepared via in situ epoxidation of natural rubber (NR) using a molar ratio of formic acid/hydrogen peroxide to isoprene unit at 0.75/0.75 with five loadings of MWCNTs, ranging from 0.5–2.5 parts per hundred parts of rubber (phr), at 50°C for 4 h. Based on Fourier transform infrared spectra, the epoxide content of ENR in the nanocomposites was about 32.5–33.2 mole%. Accordingly, the products were referred to ENR30/MWCNT nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…To determine the mol% epoxidation from the 1 H‐NMR analysis, two characteristic peaks were considered in relation with Eq. 2 ; Mol%0.25emepoxidation=[]A2.7/()A2.7+A5.14×100 where A 2.7 and A 5.14 are the integrate areas under the 1 H‐NMR peaks at about 2.7 ppm, corresponding to the epoxide proton, and at about 5.14 ppm, representing an olefinic proton, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To determine the mol% epoxidation from the 1 H‐NMR analysis, two characteristic peaks were considered in relation with Eq. 2 ; Mol%0.25emepoxidation=[]A2.7/()A2.7+A5.14×100 where A 2.7 and A 5.14 are the integrate areas under the 1 H‐NMR peaks at about 2.7 ppm, corresponding to the epoxide proton, and at about 5.14 ppm, representing an olefinic proton, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It is well established that many desirable properties of rubber products can be achieved through rubber/rubber blend , rubber/polymer blend and rubber composites . It has been reported that latex blending offers compatible or miscible blend without phase separation and flocculation .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the products from NRL show some weaknesses such as low modulus, barrier properties and electrical properties that affect the quality of the natural rubber (NR) products. Consequently, many attempts have been made to use a reinforcing filler such as graphene oxide [ 5 ], multiwalled carbon nanotube [ 6 ], organoclay [ 7 , 8 ], carbon black [ 9 ], silica [ 10 ], cassava starch [ 11 ], and carbon fiber [ 12 ], to improve NR properties. The incorporation of bio-fillers from renewable resources into NRL could result in new biocomposites with enhanced features and biodegradability, so it is of interest to study the possibility of using chitosan (CT) as a reinforcing filler for NRL.…”
Section: Introductionmentioning
confidence: 99%